MAINTENANCE AND REPAIR TECHNIQUES IN COMPUTER DISK DRIVES IBM PC - Sugeng Riyadi; Ir. Aqwam Rosadi K. MM (Jurnal Sistem Komputer, 1998)
A computer system IBM PC / XT is full when it is said to have the system unit,display monitor, printer and the subject-the subject of other supporters who canfunction well as it should. Each concerning each having a separate function that isintegrated between the subject with one another.At about that there are damages / defects must be checked where the damagedcomponents. It is necessary to replace defective parts with a good computer system toIBM PC / XT to function properly as desired by the user.